PERANCANGAN SISTEM INFORMASI PERMINTAAN LIPUTAN BERBASIS WEBSITE PADA PERUSAHAN CENDRAWASIH WIPUTRA MANDIRI, KOTA SORONG - Matheus Supriyanto Rumetna; Tirsa Ninia Lina (Electro Luceat, 2021)
The Cendrawasih Wiputra Mandiri company is a cable and channel TV company located in Sorong City, precisely on Danau Maninjau road, Number 19 Rufei. This company which is engaged in broadcasting and broadcasting services continues to develop its business while maintaining the quality of its broadcasts to customers so that customers can still get satisfaction. In these companies, requests for coverage are still manual, where customers come to the office or through marketing, causing ineffective and efficient services. The purpose of this research is to design a website-based information request information system to make it easier for customers to request coverage. The system design method used is Method V with a design model using Data Flow Diagrams. The software used in this research is Adobe Photoshop as a system framework, Brackets for coding and display design, XAMPP as a database server, Composer as a place to download Laravel, and Mozilla Firefox as a browser to run the system. The results of system design in this study display the main page, login form, coverage request form, price information, coverage category information, contact information and information about us. Then the results of the system design were tested using the Blackbox and the results went well (valid).